KEPENTINGAN INDONESIA DALAM MENGAMBIL ALIH FLIGHT INFORMATION REGION (FIR) DARI SINGAPURA - Alwafi Ridho Subarkah (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2019)
Each state should maintain their sovereignty as a whole, especially on their territory which includes air, land and sea. However, Indonesia has not been fully sovereign in its airspace. For instance, Air Traffic Control (ATC) is still controlling flight identification zones in Western Indonesia, such as Serawak, Tanjung Pinang, Malacca Peninsula, Natuna and Riau Islands. This was a threat because when the Indonesian Armed Forces aircraft on patrol and training had to report to the Singapore ATC, economically it also required Indonesia to pay fees to Singapore if it passed through the area.This research aims to shows the Indonesian interest in taking over the Flight Information Region (FIR) in a bid to safeguard the sovereignty of Indonesia. The method in this research is qualitative method that describes and explains research problems related to the topics discussed and triangulates methods and data. This research uses the concept of national interest, where the state has ability to protect and defend its national interests sovereignly by making various policies.The results of this research show that the interest of Indonesia is to fully maintain their sovereignty by making Law No. 1 of 2009 concerning about Aviation and Government Regulation No. 4 of 2018 concerning Security of the Republic of Indonesia Airspace, improving human resources and technology. On an international scale, efforts continue to be made through the International Civil Aviation Organization (ICAO) so that the FIR managed by the Singapore ATC can be managed by Indonesia. Thus, any diplomatic and foreign aircraft security clearance processed through the Indonesian government. Keywords: National Interest, Sovereignty, Air Sovereignty, Territory Control Abstrak Kedaulatan setiap negara harus dijaga secara keseluruhan, pada konteks ini adalah kedaulatan wilayah yang mencakup udara, darat dan laut. Namun Indonesia belum berdaulat dalam udara sepenuhnya. Bagian barat Indonesia, seperti Serawak, Tanjung Pinang, Semenanjung Malaka, Natuna dan Kepulauan Riau dalam mengelola zona identifikasi penerbangan dikuasai oleh Air Traffic Control (ATC) Singapura. Hal ini menjadi ancaman karena saat pesawat Tentara Nasional Indonesia dalam patroli maupun latihan melapor ke Singapura, secara ekonomi juga mengharuskan Indonesia untuk membayar biaya kepada Singapura jika melewati wilayah tersebut. Tujuan penelitian yaitu menunjukkan kepentingan Indonesia dalam mengambil alih Flight Information Region (FIR) sebagai upaya untuk menjaga kedaulatan Indonesia. Metode dalam penelitian ini yaitu metode kualitatif yang mendeskripsikan dan menjelaskan permasalahan penelitian terkait topik yang dibahas dan melakukan triangulasi metode dan data. Penelitian ini menggunakan konsep national interest yaitu kemampuan negara dalam melindungi maupun mempertahankan kepentingan nasionalnya secara berdaulat dengan mengeluarkan berbagai kebijakan. Hasil penelitian ini, kepentingan Indonesia adalah menjaga kedaulatan sepenuhnya dengan membuat Undang-Undang No. 1 Tahun 2009 tentang Penerbangan serta Peraturan Pemerintah No. 4 Tahun 2018 tentang Pengamanan Wilayah Udara Republik Indonesia, meningkatkan sumber daya manusia dan meningkatkan teknologi. Pada skala internasional terus dilakukan upaya melalui International Civil Aviation Organization (ICAO) agar FIR yang dikelola oleh ATC Singapura dapat dikelola oleh Indonesia sehingga izin diplomatik dan izin keamanan pesawat asing melalui pemerintah Indonesia. Kata Kunci: Kepentingan Nasional, Kedaulatan, Kedaulatan Udara, Pengelolaan Wilayah